Who watches the watchmen? Evaluating evaluations of El Sistema. Issue 3 (13th June 2018) - Baker, Geoffrey; Bull, Anna; Taylor, Mark
Abstract : Within the growing field of publications on El Sistema and Sistema-inspired programmes around the world, a marked divide can be observed between the findings of critical academic studies and commissioned evaluations. Using evaluations of El Sistema in Venezuela and Aotearoa New Zealand as our principal case studies, we argue that this gulf can be explained at least partly by methodological problems in the way that some evaluations are carried out. We conclude that many Sistema evaluations display an alignment with advocacy rather than explorative research, and that the foundation for El Sistema's claims of social transformation is thus weak.